STRUCTURAL MEASURES OF COMPANIES IN RUSSIA’S STATE PROPERTY - D. A. Klimenko; I. V. Munerman; V. E. Fedotov (Стратегические решения и риск-менеджмент)
We consider structural measures of companies whose stocks are the federal property. Various ways concerning developing efficiency rankings for those companies are also considered.